The Effect of Simvastatin on Gut Microbiota and Lipid Metabolism in Hyperlipidemic Rats Induced by a High-Fat Diet - Zhang, Qing; Fan, Xiaoyun; Ye, Rui; Hu, Yuzhong; Zheng, Tingting; Shi, Rui; Cheng, Wenjian; Lv, Xucong; Chen, Lijiao; Liang, Peng (Frontiers in Pharmacology, 2020)
The objective of this study was to investigate the effects of simvastatin (SIM) on lipid metabolism disorders and gut microbiota in high-fat diet-induced hyperlipidemic rats. The obtained results revealed that feeding rats with SIM (20 mg/kg/day) significantly decreased serum lipid level and inhibited hepatic lipid accumulation and steatosis. Histological analysis further indicated that SIM reduced lipid deposition in adipocytes and hepatocytes in comparison with that of the HFD group. The underlying mechanisms of SIM administration against HFD-induced hyperlipidemia were also studied by UPLC-Q-TOF/MS-based liver metabonomics coupled with pathway analysis. Metabolic pathway enrichment analysis of liver metabolites with significant difference in abundance indicated that fatty acids metabolism and amino acid metabolism were the main metabolic pathways altered by SIM administration. Meanwhile, operational taxonomic units (OTUs) analysis revealed that oral administration of SIM altered the composition of gut microbiota, including Ruminococcaceae (OTU960) and Lactobacillus (OTU152), and so on. Furthermore, SIM treatment also regulated the mRNA levels of the genes involved in lipid and cholesterol metabolism. Immunohistochemistry (IHC) analysis of the liver-related proteins (CD36, CYP7A1 and SREBP-1C) showed that oral administration of SIM could regulate the levels the protein expression related to hepatic lipid metabolism.